Fully inkjet-printed two-dimensional material field-effect heterojunctions for wearable and textile electronics. Issue 1 (December 2017) - Carey, Tian; Cacovich, Stefania; Divitini, Giorgio; Ren, Jiesheng; Mansouri, Aida; Kim, Jong; Wang, Chaoxia; Ducati, Caterina; Sordan, Roman; Torrisi, Felice
Abstract Fully printed wearable electronics based on two-dimensional (2D) material heterojunction structures also known as heterostructures, such as field-effect transistors, require robust and reproducible printed multi-layer stacks consisting of active channel, dielectric and conductive contact layers. Solution processing of graphite and other layered materials provides low-cost inks enabling printed electronic devices, for example by inkjet printing. However, the limited quality of the 2D-material inks, the complexity of the layered arrangement, and the lack of a dielectric 2D-material ink able to operate at room temperature, under strain and after several washing cycles has impeded the fabrication of electronic devices on textile with fully printed 2D heterostructures. Here we demonstrate fully inkjet-printed 2D-material active heterostructures with graphene and hexagonal-boron nitride (h-BN) inks, and use them to fabricate all inkjet-printed flexible and washable field-effect transistors on textile, reaching a field-effect mobility of 91 cm2 V−1 s−1, at low voltage (<5 V). This enables fully inkjet-printed electronic circuits, such as reprogrammable volatile memory cells, complementary inverters and OR logic gates. Heterojunction structures based on 2D materials show promise for wearable and textile electronics. Here, the authors demonstrate fully inkjet-printed hetero junctions of graphene and h-BN as a platform for FET-based smart electronics on wearable and washable textile substrates.